Sviluppo, realizzazione e test sperimentali su strada di un powertrain ibrido a celle a combustibile e batterie per un bus urbano e sub-urbano - Andaloro, Laura; Furgiuele, Franco; Fragiacomo, Petronilla (My University, 2019)
In Europe, the transport sector is responsible for almost 30% of greenhouse gas emissions and is the main cause of air pollution in cities. Among the various measures, a better urban planning, technological improvements and a wider use of alternative fuels are currently underway. Today the electrification of vehicles is an important element of the approach to sustainable mobility, and for this reason the research is aimed at developing zero/low emissions vehicles characterized by innovative carbon-free devices. The main problem of electric vehicles is the low capacity of batteries that means low range of autonomy. Furthermore, long charging time is an important obstacle if compared to refuelling time of traditional internal combustion vehicles. On the other hand, hybrid vehicles (combustion engine and electric motor), thanks to the presence of an electrical component, allow to obtain a fuel saving and to exploit the existing infrastructure, but they still depend entirely on the oil both to charge batteries and to supply the combustion engine. The technology of fuel cells, and in particular the polymer-type fuel cells (PEFCs - Polymer Electrolyte Fuel Cells), characterized by low noise levels, no pollutants, high energy density and short starting time can help the development of zero emission vehicles reducing batteries problems and ensuring a secure energy supply. Several vehicles based only on hydrogen technologies have been proposed, but the costs of fuel cells and hydrogen systems limit their market penetration. The roadmap on electric and plug-in electric vehicles (Technology Roadmap - Electric and Plug-in Hybrid Electric Vehicles) identifies, for the first time, a detailed scenario for the evolution of electric hybrid vehicles with fuel cells and batteries (FCHEV) that offer the possibility of combining the advantages of both technologies. In this context the present PhD thesis proposes the study concerning the development, realization and test of a hybrid electric minibus powered by batteries and fuel cells. In the first part, the description of the PEFC fuel cell technology and the analysis of the state of the art of PEFC applications in the transport sector has been treated and some information about applications in stationary and portable applications have been reported (Chapter 1). Before discussing the proposed powertrain for the hybrid electric minibus a vehicles classification has been shown, conventional hybrid powertrains (electric motor and internal combustion engine) in different possible hybridization levels, pure electric powertrains and finally hybrid electric powertrains (batteries and fuel cells). With reference to this latter powertrain, the state of the art of fuel cell buses has been analyzed and, finally, the selected architecture for the proposed powertrain has been introduced (Chapter 2). In order to design and develop the proposed powertrain different experimental tests on batteries and FC have been carried out at CNR ITAE laboratories (Institute of Advanced Energy Technologies of National Research Council of Italy). Two different types of batteries, suitable for vehicles applications, have been compared: LiPo and LiFePO4. The most suitable battery for installation on board has been chosen. At the same time a PEFC system has been selected from the market and its performance have been evaluated by using an equivalent 2 kW short stack (Chapter 3). Starting from selection of two principal devices (batteries and FC system) the innovative powertrain has been realized at CNR ITAE. The range extender configuration has been considered optimal for an urban and sub-urban minibus in order to overcome limits of batteries technology. FC system works at constant power (ideal condition that preserves the FC durability) and batteries work in load following mode. Two different drive modes have been enabled: electric mode (only batteries) and hybrid mode (batteries and FC system). For the latter mode a specific energy flow strategy has been developed defining the technical intervention of FC as a function of batteries SOC (State of Charge) (Chapter 4). Finally the powertrain has been installed on the minibus and different tests on the road have been carried out implementing real driving duty cycles. The minibus has been lent to the Capo d’Orlando Municipality (ME) with the aim to offer a free service to citizens. The purpose of this use is the assessment of reliability, autonomy and the management and control logic of energy flows, as well as making a free service to the municipality of Capo d'Orlando that has inserted the vehicle within its own mobility planning. Furthermore, specific cycles have been implemented to verify the limit conditions, that means verify the maximum range of autonomy of the vehicle, both in electric mode (i.e. with only the presence of batteries) and in hybrid mode (batteries and fuel cell) (Chapter 5).
Dottorato di Ricerca in Ingegneria Civile ed Industriale. Ciclo XXXI
Keywords: Celle a combustibile; Trasporti urbani; Gruppo propulsore